A theoretical evaluation of the effect of netropsin binding on the reactivity of DNA towards alkylating agents. - Zakrzewska, K (1983)
The effect of netropsin binding on the electrostatic potential of DNA reactive sites is presented. Calculations are performed for atoms N7 and O6 of guanine, N3 and N7 of adenine of model, 25 base pair long, DNA-netropsin complexes. An important weakening of the potential is found spreading along all the oligonucleotide chain studied. The results are discussed in connection with the inhibitory effect of a related ligand, distamycin A, on DNA methylation.